Delving into Molecular Pathways: Analyzing the Mechanisms of Action of Monoclonal Antibodies Integrated in IMGT/mAb-DB for Myasthenia Gravis - Rebecca Golfinopoulou; Véronique Giudicelli; Taciana Manso; Sofia Kossida (Vaccines, 2023)
Background: Myasthenia Gravis (MG) is a rare autoimmune disease presenting with auto-antibodies that affect the neuromuscular junction. In addition to symptomatic treatment options, novel therapeutics include monoclonal antibodies (mAbs). IMGT®, the international ImMunoGeneTics information system®, extends the characterization of therapeutic antibodies with a systematic description of their mechanisms of action (MOA) and makes them available through its database for mAbs and fusion proteins, IMGT/mAb-DB. Methods: Using available literature data combined with amino acid sequence analyses from mAbs managed in IMGT/2Dstructure-DB, the IMGT® protein database, biocuration allowed us to define in a standardized way descriptions of MOAs of mAbs that target molecules towards MG treatment. Results: New therapeutic targets include FcRn and molecules such as CD38, CD40, CD19, MS4A1, and interleukin-6 receptor. A standardized graphical representation of the MOAs of selected mAbs was created and integrated within IMGT/mAb-DB. The main mechanisms involved in these mAbs are either blocking or neutralizing. Therapies directed to B cell depletion and plasma cells have a blocking MOA with an immunosuppressant effect along with Fc-effector function (MS4A1, CD38) or FcγRIIb engager effect (CD19). Monoclonal antibodies targeting the complement also have a blocking MOA with a complement inhibitor effect, and treatments targeting T cells have a blocking MOA with an immunosuppressant effect (CD40) and Fc-effector function (IL6R). On the other hand, FcRn antagonists present a neutralizing MOA with an FcRn inhibitor effect. Conclusion: The MOA of each new mAb needs to be considered in association with the immunopathogenesis of each of the subtypes of MG in order to integrate the new mAbs as a viable and safe option in the therapy decision process. In IMGT/mAb-DB, mAbs for MG are characterized by their sequence, domains, and chains, and their MOA is described.